Agents of resistance and revival? Local election monitors and democratic fortunes in Asia. Issue 1 (2nd January 2021) - Grömping, Max
ABSTRACT: Cultural and political economy theories linking a vibrant civil society to democratic outcomes expect domestic election monitors to provide a vaccine against democratic backsliding. The empirical track record of such groups, however, is mixed. Drawing from theories of interest representation and social movement research, I present a novel approach to studying the effect of observer groups. Conceptualizing monitors as agenda-builders, I contend that their potential impacts rely on two factors neglected by previous studies: access to the public's agenda, and access to policymakers. I test the impact of election monitoring on electoral integrity using cross-national time-series data of all democratic backsliding and revival episodes in Asia from 1950 to 2018. I find that domestic monitors do have more than a placebo effect, but that their capacities to immunize against democratic regression are modest at best. When neither access to the public's agenda nor access to policymakers are present, monitors are unlikely to halt backsliding. However, public attention becomes an effective resource where groups have policy access. This adds to studies of democratic backsliding, election monitoring, and interest groups.